Performance Development Of Wrestlers In Sport Education Centre - Osman İmamoğlu; Hüseyin Aslan; Yener Aksoy (Selcuk University, 2020)
The aim of this study is to determine the changes in the physical and motoric characteristics of wrestlers in wrestling education Centers in the first year. The average age of the wrestling training center wrestlers was 12.05 years in the first measurement and the last measurement was 13.05 years. There was a significant change in age and height of wrestlers in one year period (p lt;0.001). The change in body weights was found to be insignificant (p gt; 0.05). The changes in squat jump, long jump, hand grip strength, flexibility, shuttle pull, 30 meter speed, aerobic and anaerobic power values of the wrestlers were significant in one year period (p lt;0.05 and p lt;0.001). There was no significant difference in throwing health ball in one year period (p gt; 0.05). In the present study, the differences between the average max V02, 30 meter sprint, number of shuttles in 30 seconds and sit and reach flexibility values of wrestlers within a year were found to be statistically significant (p lt;0.05 and p lt;0.001). Conclusion: Motor performance parameters of speed, abdominal strength, flexibility, anaerobic strength and aerobic endurance values of the wrestlers increased during the one year period. There was no significant increase in shoulder - arm throw strength. Particular attention should be given to arm traction movements, in addition to pushing from arms and shoulder area exercises during wrestlers' training.